A Re-Examination of Traditional Hypotheses about the Term Structure of Interest Rates - Cox, John C.; Ingersoll, Jonathan E.; Ross, Stephen A. (Journal of Finance, 1981)
The term structure of interest rates is an important subject to economists, and has a long history of traditions. This paper re-examines many of these traditional hypotheses while employing recent advances in the theory of valuation and contingent claims. We show how the Expectations Hypothesis and the Preferred Habitat Theory must be reformulated if they are to obtain in a continuous-time, rational-expectations equilibrium. We also modify the linear adaptive interest rate forecasting models, which are common to the macroeconomic literature, so that they will be consistent in the same framework.